2021
DOI: 10.3390/s21217022
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Performance of Graphene Flexible Pressure Sensor with Micro/Nano Structure

Abstract: Laser-induced graphene (LIG) has been widely used in flexible sensors due to its excellent mechanical properties and high conductivity. In this paper, a flexible pressure sensor prepared by bionic micro/nanostructure design and LIG mass fraction regulation is reported. First, prepared LIG and conductive carbon paste (CCP) solutions were mixed to obtain a conductive polymer. After the taro leaf structure was etched on the surface of the aluminum alloy plate by Nd:YAG laser processing, the conductive polymer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…More importantly, compared with traditional films, inorganic nanostructures are easier to combine with flexible materials [51]. Nanomaterials, carbon nanofibers, carbon black, and graphene are often combined with elastomers such as polydimethylsiloxane (PDMS), eco flex, and rubber to make polymer composite sensors [52]. Based on this premise, we found that graphene is a two-dimensional nanostructured material that can be synthesized in a large area [48,53,54].…”
Section: Application Of Graphene In Physical Sensorsmentioning
confidence: 99%
See 4 more Smart Citations
“…More importantly, compared with traditional films, inorganic nanostructures are easier to combine with flexible materials [51]. Nanomaterials, carbon nanofibers, carbon black, and graphene are often combined with elastomers such as polydimethylsiloxane (PDMS), eco flex, and rubber to make polymer composite sensors [52]. Based on this premise, we found that graphene is a two-dimensional nanostructured material that can be synthesized in a large area [48,53,54].…”
Section: Application Of Graphene In Physical Sensorsmentioning
confidence: 99%
“…The research of flexible pressure sensors mainly changes the microstructure of the conductive layer of the sensor to improve the sensing performance of the sensor [52,55]. The following will introduce specific examples of several graphene flexible pressure sensors to reflect the role of graphene materials in flexible pressure sensors.…”
Section: Application Of Graphene In Physical Sensorsmentioning
confidence: 99%
See 3 more Smart Citations